The impact of social media addiction on state self-esteem; a cross-sectional study in university students from Samborondón, Ecuador - Oleas Rodríguez, Daniel; López-Barranco Pardo, Gonzalo (European Public & Social Innovation Review, 2024)
Introduction: The rise of social media has transformed social interactions, becoming essential in the lives of young people. Its excessive use raises concerns about negative repercussions on mental health, especially on self-esteem, which is crucial for psychological well-being and academic success. Methodology: This cross-sectional quantitative study investigated the influence of social media addiction on the state of self-esteem among 521 psychology students, selected by convenience. The Social Media Addiction Scale - Student Form (SMAS-SF) and the State Self-Esteem Scale (SSES) were used. Results: The results indicate that problems arising from social media use (β=-0.42, p<.001) and the obsession with being connected (β=-0.49, p=0.01) are significant predictors of lower state self-esteem, explaining 10% of the variance in state self-esteem. Discussions: Social media addiction has a moderately negative impact on the self-esteem of university students, which has negative implications for well-being. Conclusions: The need for specific interventions to mitigate these effects is highlighted. Further research is recommended to develop and evaluate the effectiveness of such interventions in the long term.